The effects of arts and crafts therapy on post-stroke executive dysfunction: a pilot randomized control test - Yun, Ruisheng; Zhou, Huanxia; Gray, Julie McLaughlin; Cheng, Jia; Zhao, Zhongzhi (Frontiers in Stroke, 2023)
Background Executive function is an important determinant of independent living among stroke survivors. Patients with post-stroke executive dysfunction (PSED) have a lower engagement in therapy activities and reduced independent living abilities. One potential method for improving executive function and engagement is arts and crafts therapy (ACT). This study aimed to explore the effects of ACT on patients with PSED. Methods The study was a pilot randomized controlled trial (RCT) with two groups: an experimental intervention group receiving ACT combined with individual rehabilitation therapy (IRT) and an active control group receiving IRT only. Fifty-seven patients with PSED participated. Outcome measures included the Trail Making Test (parts A and B), the Stroop test, the Tower of Hanoi (TOH), and the Lawton–Brody Instrumental Activities of Daily Living Scale. Two groups were compared at baseline and 4 weeks after the completion of the training. Results There were significant differences in the Trail Making Test part A (TMT-A; time; p < 0.01), the TMT part B (TMT-B; p < 0.05), the TMT-B (errors; p < 0.01), and the Stroop test (time; p < 0.01) between the experimental and the control group after 4 weeks. There were no significant differences in TMT-A (errors), Stroop test (errors), TOH, and Instrumental Activities of Daily Living Scale. Conclusion The therapeutic use of arts and crafts could be an effective intervention to improve executive function and self-efficacy for stroke survivors. Clinical trial registration http://www.chictr.org.cn; Identifier: ChiCTR2200063547.